PERAN NYAMBAI SEBAGAI IDENTITAS DAN TRADISI BUDAYA LAMPUNG - Arika Herlandani; Puspa, Tiara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Nyambai Dance is a cultural heritage of the Lampung people which is full of the principles of politeness, togetherness and honor. However, its existence began to be modernized, especially in the language and oral literature it included. The aim of this research is to explain the role of Nyambai as Lampung's cultural identity and develop strategies to preserve it. Qualitative descriptions are used through observation, interviews and literature study. The results of this research show that Nyambai functions as a symbol of identity, a medium for interacting with other people, and a tool for spreading cultural values. The poetry and pantun strengthen the identity of the Lampung language and contain a moral message. Art learning and local content activities in schools can help preserve culture. Therefore, Nyambai shows the identity of the Lampung people as more than just traditional entertainment.